The development of adolescents' loneliness during the COVID-19 pandemic: The role of peer status and contact with friends - Lorijn Sofie J.; Laninga-Wijnen Lydia; Engels Maaike C.; Lodder Gerine M.A.; Veenstra René (Public Library of Science, 2025)
The COVID-19 measures raised societal concerns about increases in adolescents’ loneliness. This study examined trajectories of adolescents’ loneliness during the pandemic, and whether trajectories varied across students with different types of peer status and contact with friends. We followed 512 Dutch students (Mage = 11.26, SD = 0.53; 53.1% girls) from before the pandemic (Jan/Feb 2020), over the first lockdown (March-May 2020, measured retrospectively), until the relaxation of measures (Oct/Nov 2020). Latent Growth Curve Analyses (LGCA) showed that average levels of loneliness declined. Multi-group LGCA showed that loneliness declined mostly for students with a victimized or rejected peer status, which suggests that students with a low peer status prior to the lockdown may have found temporary relief from negative peer experiences at school. Students who kept all-round contact with friends during the lockdown declined in loneliness, whereas students who had little contact or who did not (video) call friends did not.